Response of potato (Solanum tuberosum L.) to the combined application of organic and inorganic fertilizers at Chena district, South Western Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
Low level or no use of organic and inorganic fertilizers and serious imbalances soil nutrients, depressed potato yields and pose accelerated mining of native soil nutrients. Present on-farm studies was undertaken to observe the combined effects of FYM and compost along with inorganic fertilizers, particularly NPSB on potato production. The experiment comprised of seven treatments: No fertilizer, recommended NP (115 kg N and 92 kg ha-1 P2O5), NPSB (115 kg N and 92 kg P2O5, 6.5 kg S. and 0.71 kg B ha-1), 10 tone FYM ha-1, 10 tone compost ha-1, 5 tone FYM + 50% NPSB (57.5 kg N and 92 kg P2O5 ha-1), and 5 tone compost + 50% NPSB ha-1 were arranged in RCBD with three replications. The yield and yield components were collected and subjected to mean separation and economic analysis. The analysis of variance indicated that either applied organic and inorganic fertilizers combined or alone significantly (p ≤ 0.05) improved potato yield at Chena. Full dose of each FYM and compost, recommended NP rate and NPSB gave similar potato yield. The highest average marketable and total fresh potato tuber yield (27.44, 27.92 t ha-1, respectively) were recorded by combined application of 5 t FYM ha-1 with 50% NPSB (115 kg N and 92 kg P2O5, 6.5 kg S. and 0.71 kg B ha-1) which is economically acceptable with MRR (1239.7%), whereas the lowest tuber yield (14.45 t ha-1) was obtained from unfertilized plot. Hence, combined application of 50% FYM and 50% NPSB proved best potato yield in the study area.Int. J. Agril. Res. Innov. Tech. 12(1): 18-22, June 2022